METODE PELAKSANAAN TERAPI KELOMPOK (GROUP THERAPY) - Trinurmi, Sitti (Jurusan Bimbingan dan Penyuluhan Islam, 2023)
Group therapy is a form of psychotherapy where a group of patients come together to engage in discussions facilitated or directed by a trained therapist or mental health professional. Group therapy is a treatment method where individuals meet at specified intervals under the guidance of qualified personnel. The focus of group therapy is to promote self-awareness, improve interpersonal relationships, bring about personal changes, or a combination of these goals. Various specific methods are employed in the implementation of group therapy, such as psychodrama, role-playing (royal playing), and encounter groups.